고가용성 클라우드 컴퓨팅 구축을 위한 그리드 소프트웨어 아키텍처 - 이병엽(Byoung-Yup Lee); 박준호(Junho Park); 유재수(Jaesoo Yoo) (한국콘텐츠학회 논문지, 12(2), 2012)
Currently, cloud computing technology is being supplied in various service forms and it is becoming a ground breaking service which provides usage of storage service, data and software while user is not involved in technical background such as physical location of service or system environment. cloud computing technology has advantages that it can use easily as many IT resources as it wants freely regardless of hardware issues required by a variety of systems and service level required by infrastructure. Also, since it has a strength that it can choose usage of resource about business model due to various internet-based technologies, provisioning technology and virtualization technology are being paid attention as main technologies. These technologies are ones of important technology elements which help web-based users approach freely and install according to user environment. Therefore, this thesis introduces software-related technologies and architectures in an aspect of grid for building up high availability cloud computing environment by analysis about cloud computing technology trend. 최근, 클라우드 컴퓨팅 기술은 다양한 서비스의 형태로 제공이 되며, 사용자는 서비스의 물리적인 위치나, 시스템 환경과 같은 부분들을 관여하지 않고, 스토리지 서비스, 데이터의 사용, 소프트웨어의 사용들을 제공하는 획기적인 서비스로 거듭나고 있다. 클라우드 컴퓨팅 기술들은 인프라스트럭처에서 요구되는 서비스의 수준, 다양한 시스템에서 요구되는 하드웨어적인 문제들을 벗어서 자유스럽게 원하는 만큼의 IT 리소스를 쉽게 사용할 수 있는 장점을 가지고 있다. 또한 인터넷 기반의 다양한 기술들을 기반으로 비즈니스 모델에 대한 자원의 사용을 자유스럽게 선택할 수 있는 장점을 가지고 있어 무엇보다도 능동적인 자원 확장을 위한 프로비져닝 기술과 가상화 기술들이 주요한 기술로 주목 받고 있다. 이러한 기술들은 웹 베이스의 사용자들이 자유롭게 접근하고, 사용자 환경에 맞도록 설치가 가능하게 지원하는 중요한 기술 요소들 중의 하나이다. 따라서 본 논문은 클라우드 컴퓨팅 기술 동향에 대한 분석을 통해 고 가용성 클라우드 컴퓨팅 환경을 구축하기 위한 그리드 측면에서의 소프트웨어 관련 기술과 아키텍처를 소개 한다.